Utilizing Low-Volume Aqueous Acoustic Transfer with the Echo 525 to Enable Miniaturization of qRT-PCR Assay. (February 2016) - Agrawal, Sony; Cifelli, Steven; Johnstone, Richard; Pechter, David; Barbey, Deborah A.; Lin, Karen; Allison, Tim; Agrawal, Shree; Rivera-Gines, Aida; Milligan, James A.; Schneeweis, Jonathan; Houle, Kevin; et al.
Quantitative reverse transcription PCR (qRT-PCR) is a valuable tool for characterizing the effects of inhibitors on viral replication. The amplification of target viral genes through the use of specifically designed fluorescent probes and primers provides a reliable method for quantifying RNA. Due to reagent costs, use of these assays for compound evaluation is limited. Until recently, the inability to accurately dispense low volumes of qRT-PCR assay reagents precluded the routine use of this PCR assay for compound evaluation in drug discovery. Acoustic dispensing has become an integral part of drug discovery during the past decade; however, acoustic transfer of microliter volumes of aqueous reagents was time consuming. The Labcyte Echo 525 liquid handler was designed to enable rapid aqueous transfers. We compared the accuracy and precision of a qPCR assay using the Labcyte Echo 525 to those of the BioMek FX, a traditional liquid handler, with the goal of reducing the volume and cost of the assay. The data show that the Echo 525 provides higher accuracy and precision compared to the current process using a traditional liquid handler. Comparable data for assay volumes from 500 nL to 12 µL allowed the miniaturization of the assay, resulting in significant cost savings of drug discovery and process streamlining.